Marine Cyanobacteria: A Source of Lead Compounds and their Clinically-Relevant Molecular Targets - Lik Tong Tan; Ma Yadanar Phyo (Molecules, 2020)
The prokaryotic filamentous marine cyanobacteria are photosynthetic microbes that are found in diverse marine habitats, ranging from epiphytic to endolithic communities. Their successful colonization in nature is largely attributed to genetic diversity as well as the production of ecologically important natural products. These cyanobacterial natural products are also a source of potential drug leads for the development of therapeutic agents used in the treatment of diseases, such as cancer, parasitic infections and inflammation. Major sources of these biomedically important natural compounds are found predominately from marine cyanobacterial orders Oscillatoriales, Nostocales, Chroococcales and Synechococcales. Moreover, technological advances in genomic and metabolomics approaches, such as mass spectrometry and NMR spectroscopy, revealed that marine cyanobacteria are a treasure trove of structurally unique natural products. The high potency of a number of natural products are due to their specific interference with validated drug targets, such as proteasomes, proteases, histone deacetylases, microtubules, actin filaments and membrane receptors/channels. In this review, the chemistry and biology of selected potent cyanobacterial compounds as well as their synthetic analogues are presented based on their molecular targets. These molecules are discussed to reflect current research trends in drug discovery from marine cyanobacterial natural products.